IoT di Dapur Milenial, Harapan dan Tantangan Masa Depan - Nurwati, Tri (Jurnal Sociohumaniora Kodepena (JSK), 2024)
This study aims to examine how IoT is one of the industrial technologies serving human interests that will make human life more efficient. And how future technologies could be disastrous, such as lack of privacy. This progress indicates that it is becoming more modern and its long-term impact needs to be analyzed, so it is hoped that there will be a lot of research in various fields related to IoT challenges in the future. Also, the author hopes to increase women's knowledge about technology that will boom in the future.Internet of Things (IoT) makes people's lives smarter and modern. IoT can be applied in various activities, including activities in the kitchen. The kitchen is one of the places that has many technological advances in this millennial era, so rearranging the kitchen with a touch of technology goes hand in hand with the IoT revolution. This paper discusses IoT applications in the kitchen, especially safeguarding the use of gas stoves and regulating air quality in the kitchen. IoT technology in millennial kitchens can be used to remotely monitor kitchens